POLYMORPHISM OF CHRONIC GLOMERULONEPHRITIS ASSOCIATION WITH ADPRT1 GENE VAL762ALA - Kamyshova, E. S.; Shvetsov, M. Yu; Shestakov, A. E.; Kutyrina, I. M.; Nosikov, V. V. (Alʹmanakh klinicheskoĭ medit͡s︡iny, 2016)
Association of polymorphic ADPRT1 gene Val762Ala marker, encoding poly(ADP-ribose)polymerase-l, with the development, course and progress of chronic glomerulonephritis was revealed during investigation. The risk of the chronic glomerulonephritis development is higher in patients-carriers of Val-allele and Val/Val-genotype and lower in those with Ala-allele and Ala/Ala-genotype.